SYMBOLISM AND METAPHORS IN DIAN PURNOMO'S NOVEL 'PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM' - Heny Friantary; Ade Bayu Saputra; Hendro Ade Saputra (Leksema: Jurnal Bahasa dan Sastra, 2025)
Literary texts often serve as spaces for ideological articulation conveyed through language and symbols. In the context of Indonesian literature, the novel Perempuan yang Menangis kepada Bulan Hitam, written by Dian Purnomo, presents a powerful narrative addressing gender inequality and the persistence of patriarchal culture. This qualitative library study aimed to analyze the symbolic and metaphorical expressions in the novel using Michael Riffaterre’s semiotic theory. Through heuristic and hermeneutic reading stages, along with hypogram tracing, this study reveals how the novel implicitly yet sharply voices resistance against patriarchal domination. The analysis results indicate that symbols such as ‘red pool’, ‘curse’, and ‘ancestral sin’ as well as metaphors like ‘tiger’s cage’ and ‘the price of freedom’, function not merely as aesthetic ornaments but as ideological devices exposing systemic violence, social taboos, and cultural repression of women. The semiotic reading demonstrates that the novel’s symbols and metaphors construct a narrative of resistance that disrupts the dominant cultural hypogram. Thus, literature can serve as a medium for critical awareness and as a means of conveying socio-political critiques against gender-based injustice.